KONSEP AKHLAK SEORANG PESERTA DIDIK DALAM MENCARI ILMU MENURUT KIAI AHMAD SAKHOWI AMIN (Kajian Kitab Miftah Al Akhlaq) - A. Rifqi Hanif; Abdul Khobir (IAIN Pekalongan, 2013)
In education world, learner is a part of learning process. He or she should be guided as he or she is the object and subject that needs guidance from others to be ready to be a man or woman with strong faith and good morals for himself or herself, his or her teachers and others. A learner who has a noble character will also be able to realize the norms and values that will positively affect him or her to succed in the process of learning and teaching. With the existence of this character, he or she can tell which is good and which is not. This is very important because the moral issue is now spreading to the learners, they prefer to do things that are not good for teachers and others. Therefore it is necessary to study Moral Concepts of Students in Studying according Kyai Sakhowi Ahmad Amin (the study of the book Miftah Al Akhlaq).